Genome-wide analysis of IQD proteins and ectopic expression of watermelon ClIQD24 in tomato suggests its important role in regulating fruit shape - Dou, Junling; Duan, Shixiang; Umer, Muhammad Jawad; Xie, Kuixi; Wang, Yinping; Kang, Qishuai; Yang, Sen; Yang, Luming; Liu, Dongming; Liu, Lifeng; Zhao, Fengli (Frontiers in Genetics, 2022)
The plant-specific IQ67 domain (IQD) is the largest class of calmodulin targets found in plants, and plays an important role in many biological processes, especially fruit development processes. However, the functional role of IQD proteins in the development of watermelon (Citrullus lanatus) shape remains unknown, as the IQD protein family in watermelon has not been systematically characterized. Herein, we elucidated the gene structures, chromosomal locations, evolutionary divergence, and functions of 35 IQD genes in the watermelon genome. The transcript profiles and quantitative real-time PCR analysis at different stages of fruit development showed that the ClIQD24 gene was highly expressed on 0 days after pollination. Furthermore, we found that the ectopic overexpression of ClIQD24 promoted tomato fruit elongation, thereby revealing the significance of ClIQD24 in the progression of watermelon shape. Our study will serve as a reference for further investigations on the molecular mechanisms underlying watermelon fruit shape formation.